Income inequality and private bank credit in developed economies - Virmantas Kvedaras (Publications Office of the European Union, 2017)
The influence of financial deepening on income inequality in developed economies is studied with particular interest in the European Union member states that have large penetration of bank credit. Building on the model of financially open economies (Kunieda et al, 2014) and extending its implications for the top-income shares, it is shown that a simultaneous increase in private bank credit relative to the gross domestic product (GDP) and the gap between real interest rate and GDP growth rate increases inequality, as measured by both the Gini index and the top-income shares. To establish the effect on the top-income shares, a simultaneous estimation procedure is proposed that exploits the implications of the fact that a higher income range is well-characterized by the Pareto distribution.
Keywords: D31; E51; G21; O16; O41; 330; credit; financial deepening; European Union; income inequality